Essential amino acids preserve intestinal barrier integrity via mitochondrial protection in obesity and gut inflammation - Spataro, Letizia; Ragni, Maurizio; Segala, Agnese; Vetturi, Alice; Marcotto, Giulia Sofia; Canciani, Luca; Carruba, Michele O.; Aquilani, Roberto; Collo, Ginetta; Valerio, Alessandra; Nisoli, Enzo; Ruocco, Chiara (Frontiers in Pharmacology, 2025)
ObjectiveObesity disrupts intestinal homeostasis, leading to increased permeability (“leaky gut”), mucosal inflammation, and systemic metabolic dysfunction. Mitochondrial impairment in intestinal epithelial cells (IECs) is a central driver of this process. Essential amino acids (EAAs) improve mitochondrial function in metabolic tissues, but their impact on intestinal health remains underexplored. Here, we investigated whether dietary EAAs preserve gut barrier integrity through mitochondrial protection in obesity and inflammation.MethodsMale C57BL/6N mice were fed a high-fat diet (HFD) or an isocaloric, isonitrogenous EAA-substituted HFD (HFD-EAA) for 33 weeks to assess metabolic outcomes, intestinal barrier function, inflammation, and mitochondrial biogenesis. Parallel, in vitro studies in differentiated Caco-2 cells tested an EAA formula enriched with Krebs cycle intermediates (E7), under basal and pro-inflammatory conditions (IL-1β, TNF-α, LPS).ResultsHFD-EAA supplementation prevented and reversed obesity, improved glucose tolerance, reduced mesenteric fat expansion, and preserved intestinal barrier integrity while attenuating inflammation. EAAs restored intestinal length and weight, lowered plasma calprotectin, and normalized citrulline, a biomarker of enterocyte mass. Tight and adherens junction proteins (zonulin-1, occludin, E-cadherin, claudins) were maintained, while pore-forming claudin-2 was reduced. EAAs also upregulated PGC-1α and mitochondrial electron transport chain genes in intestinal epithelial cells (IECs). Their direct effects were confirmed in vitro in Caco-2 cells, where E7 increased transepithelial electrical resistance (TEER), enhanced mitochondrial respiration, suppressed inflammation-induced glycolytic reprogramming, activated antioxidant defenses, and reduced IL8 secretion. Mechanistically, E7 promoted eNOS phosphorylation and inhibited mTORC1 signaling.ConclusionEAAs protect gut barrier integrity by sustaining mitochondrial biogenesis and function in IECs, thereby reducing obesity- and stress-induced inflammation. These findings highlight EAAs as a promising nutritional strategy to counteract mitochondrial dysfunction and prevent or reverse gut barrier disruption in obesity-related and inflammatory disorders.